2020
DOI: 10.1002/col.22560
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the color of light on the customers' perception of service quality and satisfaction in the restaurant

Abstract: The physical evidence is influential on the consumer's attitude, quality perception, and purchasing behavior. The service atmosphere within the physical evidence scope is an element that requires huge investments. Together with low-cost small changes, the physical environment could be rendered much more attractive to the consumer. Color and light are among the elements that are suitable for these changes. This research aims to determine whether the color of light in the service atmosphere affects the customer'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…To retain their sustainability in today's difficult global competitive climate, to give competitive advantage, and to create a loyal customer base in the long term, airlines should be able to deliver quality service to their consumers continually. In other words, customer satisfaction is one of the key determinants of loyalty, which is crucial to the existence and sustainability of businesses [32]. The number of studies on airline service quality has increased rapidly since its link with customer satisfaction and productivity was identified [33].…”
Section: Service Quality In the Airline Industrymentioning
confidence: 99%
“…To retain their sustainability in today's difficult global competitive climate, to give competitive advantage, and to create a loyal customer base in the long term, airlines should be able to deliver quality service to their consumers continually. In other words, customer satisfaction is one of the key determinants of loyalty, which is crucial to the existence and sustainability of businesses [32]. The number of studies on airline service quality has increased rapidly since its link with customer satisfaction and productivity was identified [33].…”
Section: Service Quality In the Airline Industrymentioning
confidence: 99%
“…Past research concluded that consumers prefer specific colors in different settings. For example, Ozkul et al (2020) study of the influence of the color of light on the customers’ perception of service quality and satisfaction in actual restaurant environments concluded that service quality perceptions were higher in red and yellow-lighted ambient than those in blue and green-lighted ambient. This study did not identify a specific color scheme for theme park settings.…”
Section: Discussionmentioning
confidence: 99%
“…To run a sustainable business in today’s tough global competitive climate and create a long-term base of loyal customers, airlines should be able to continuously provide quality food, drinks, and beverages service to their customers. Satisfaction of service users and employees are key determinants of loyalty, necessary for the existence and sustainability of business ( Özkul et al, 2020 ). Providing high-quality services to passengers and tourists can be crucial for the competitiveness, profitability increasing, and long-term growth of airlines in a highly competitive environment, which is why they must meet the expectations of their passengers to maintain business ( Arasli et al, 2020 ; Gajić et al, 2021b ; Bakır et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%